Does Patient Experience Predict 30‐Day Readmission? A Patient‐Level Analysis of HCAHPS Data. Issue 10 (25th July 2018) - Siddiqui, Zishan; Berry, Stephen; Bertram, Amanda; Allen, Lisa; Hoyer, Erik; Durkin, Nowella; Qayyum, Rehan; Wick, Elizabeth; Pronovost, Peter; Brotman, Daniel J.
Abstract : BACKGROUND: Hospital‐level studies have found an inverse relationship between patient experience and readmissions. However, based on typical survey response time, it is unclear if patients are able to respond to surveys before they get readmitted and whether being readmitted might be a driver of poor experience scores (reverse causation). OBJECTIVE: Using patient‐level Hospital Consumer Assessment of Healthcare Providers and Systems (HCHAPS) and Press Ganey data to examine the relationship between readmissions and experience scores and to distinguish between patients who responded before or after a subsequent readmission. DESIGN: Retrospective analysis of 10‐year HCAHPS data. SETTING: Single tertiary care academic hospital. PARTICIPANTS: Patients readmitted within 30 days of an index hospitalization who received an HCAHPS survey linked to index admission comprised the exposure group. This group was divided into those who responded prior to readmission and those who responded after readmission. Nonreadmitted patients comprised the control group. ANALYSIS: Multivariable‐logistic regression to analyze the association between HCHAPS and Press Ganey scores and 30‐readmission status, adjusted for patient factors. RESULTS: Only 15.8% of the readmitted patients responded to the survey prior to readmission, and their scores were not significantly different from the nonreadmitted patients. The patients who responded after readmission were significantly more dissatisfied with physicians (doctors listened 73.0% versus 79.2%, adjusted odds ratio [aOR] 0.75, P < .0001), staff responsiveness, (call button 50.0% vs 59.1%, aOR 0.71, P < .0001) pain control, discharge plan, noise, and cleanliness of the hospital. CONCLUSION: Our findings suggest that poor patient experience may be due to being readmitted, rather than being predictive of readmission.